Incoterms 1990 - International Chamber of Commerce (Paris : International Chamber of Commerce, 1990)
..."Provides a set of international rules for the interpretation of the most commonly used trade terms in foreign trade."--p.6
Commercial terms.
In English and French
"Entry into force 1st July 1990."
Keywords: Commerce -- Dictionaries; Terms of trade